Performance of Zn rechargeable cells having Polypyrrole cathodes doped with surfactant anion - W.A.D.S. S Weerasinghe; L.K. M. Madhushani; K P Vidanapathirana; K. S. Perera (Ruhuna Journal of Science, 2015)
Currently there exists a very high demand for electrochemical energy storage devices such as rechargeable cells and super capacitors due to massive increase in the use of portable electronics. At the moment this demand is mainly supplied by Li based cells. However due to high cost, rapid reactivity and issues in disposal of Li attention has diverted on non Li based cells. Zn has been identified as a good candidate to replace Li. Even though several Zn based rechargeable cells were reported, less work has been carried out on cells with conducting polymer cathode based Zn cells. In this study, performance of Zn rechargeable cells fabricated with conducting polymer Polypyrrole(PPy) doped with a surfactant anion is reported. PPy films were galvanostatically electro polymerized on to stainless steel disc and cells were assembled with a Polyvinylidenefluoride based gel polymer electrolyte having Zinc trifluoromethanesulfonate as the salt. Cells having different cathode thickness were fabricated and they were characterized using cyclic voltammetry, electrochemical impedance spectroscopy and continuous charge-discharge tests. Cells exhibit open circuit voltages between 0.9 -1.0 V. Cycling testes showed that cycleable capacity almost follow the thickness variation. Continuous charge-discharge tests revealed that the capacity decrement with the cycle number is higher in thinner films.